Fish and marine fatty acids intakes, the FADS genotypes and long-term weight gain: a prospective cohort study - Yoriko Heianza; Dianjianyi Sun; Lu Qi; Louis R Pasquale; Jian-Min Yuan; Tao Huang; Frank B Hu; Tiange Wang; Janey Wiggs; Hyon-Kyoo Choi; Jin Fang Chai; Xueling Sim; et al. (BMJ Open)
Objective We tested whether genetic variants near fatty acid desaturases gene (FADS) cluster, which were recently identified to be signatures of adaptation to fish-rich and n-3 polyunsaturated fatty acids (PUFAs)-rich diet, interacted with these dietary factors on change in body mass index (BMI).Design Three FADS variants were examined for gene-diet interactions on long-term (~10 years) changes in BMI and body weight in four prospective cohort studies.Setting Population based study.Participants 11 323 women from the Nurses’ Health Study (NHS), 6833 men from the Health Professionals Follow-up Study (HPFS) and replicated in 6254 women from the Women’s Health Initiative (WHI) and 5 264 Chinese from the Singapore Chinese Health Study (SCHS).Main outcomes Long-term (~10 years) changes in BMI and body weight.Results In the NHS and HPFS cohorts, food-sourced n-3 PUFAs intake showed interactions with the FADS rs174570 on changes of BMI (P for interaction=0.02 in NHS, 0.05 in HPFS and 0.007 in combined). Such interactions were replicated in two independent cohorts WHI and SCHS (P for interaction=0.04 in WHI, 0.02 in SCHS and 0.001 in combined). The genetic associations of the FADS rs174570 with changes in BMI increased across the tertiles of n-3 PUFAs in all the cohorts. Fish intake also accentuated the genetic associations of the FADS rs174570 with long-term changes in BMI (pooled P for interaction=0.006). Viewed differently, long chain n-3 PUFAs intake showed stronger association with long-term changes in BMI among the rs174570 T carriers (beta=0.79 kg/m2 per g, p=3×10−5) than the rs174570 non-T carriers (beta=0.16 kg/m2 per g, p=0.08). Similar results were observed for fish intake.Conclusions Our hypothesis-driven analyses provide replicable evidence that long chain n-3 PUFAs and fish intakes may interact with the FADS variant on long-term weight gain. Further investigation is needed to confirm our findings in other cohorts.